2022
DOI: 10.3390/f13081256
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interspecific Variability of Non-Structural Carbohydrates and Phenolic Compounds in Flowers of 70 Temperate Trees and Shrubs

Abstract: (1) The focus on floral functional traits and their variability has been significantly lower than when compared to other plant organs. Here, we focused on the variability of four novel floral chemical traits. We aimed to assess the level of interspecific variability of total non-structural carbohydrates (TNC) and total phenolic compounds (TPh) in the flowers of woody species. (2) We collected data on 70 species of temperate trees and shrubs. We also assessed the intraspecific level of variability by collecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…The Arboretum's comprehensive dendrological collection renders it an appealing setting for such investigations. We have previously highlighted the advantages of utilizing the Arboretum for studies on the variability of specific leaf area (Paź‐Dyderska et al., 2020 ), floral chemical and size‐related traits (Paź‐Dyderska et al., 2022 ; Paź‐Dyderska & Jagodziński, 2024 ), and seed mass (Dylewski et al., 2024 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Arboretum's comprehensive dendrological collection renders it an appealing setting for such investigations. We have previously highlighted the advantages of utilizing the Arboretum for studies on the variability of specific leaf area (Paź‐Dyderska et al., 2020 ), floral chemical and size‐related traits (Paź‐Dyderska et al., 2022 ; Paź‐Dyderska & Jagodziński, 2024 ), and seed mass (Dylewski et al., 2024 ).…”
Section: Methodsmentioning
confidence: 99%
“…We randomly selected a representative sample comprising 79 woody plant species cultivated under controlled common garden conditions (Figure S1 ), as outlined in our previous work (Paź‐Dyderska et al., 2020 , 2022 ). Our data collection spanned from March 2021 to August 2022, emphasizing the examination of fully developed flowers, leaves, and fruits free from any damage caused by fungi, herbivores, or abiotic factors like hail or drought.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, much less is known about the contribution of macronutrients to this process. However, a great interspecific heterogeneity exists in the nutrient content of plants (Ojima and Isawa, 1968;Ryder et al, 2021;Paź-Dyderska et al, 2022;Venjakob et al, 2022) and insects' feeding preferences and performance can vary in response to such variation (Raubenheimer and Simpson, 1997;Schoonhoven et al, 1998;Wetzel et al, 2016;Vaudo et al, 2020). It has even been suggested that a low macronutrient content may act as a defense against insects, by reducing survival or fecundity and by increasing exposure to natural enemies as a result of a prolonged development (Berenbaum, 1995).…”
Section: Introductionmentioning
confidence: 99%